Determinants of Mobile Money Remittance in East Africa - Correia, Oscar; Ngare, Philip; Sindiga, Durvine; Otwoma, Desmond (My University, 2017)
Globally, remittances represent an important flow of international financial resources. In the East African trading bloc, the dynamic population movements between countries has led to widespread distribution of population across the region. This has driven the demand for migrant workers to send money home. Mobile money has seen a rapid growth within individual East African countries with Kenya, Tanzania and Uganda topping the global volume of mobile money transfers. One would expect the Mobile Money Remittance within the East African region to follow a similar trend being an extension of the local service. However, its uptake across borders appears to be slow. This study seeks to identify the consumer determinants that affect the uptake of the service. The study is based on the Technology Acceptance Model which gathers insight through the lens of usefulness, ease of use, perceived cost, availability of alternatives and risk perception. Once the data was collected a Cronbach alpha was applied to ensure their reliability for the purpose. The research showed that Perceived Usefulness and Perceived Ease of Use are key drivers for the mobile international remittance. This could be expected given the mobile money background of the users. In addition, the Perceived Cost of International Mobile Remittance is a key driver of behavioral intent. There was little evidence to show that Attractiveness of Alternatives and Perceived risk actually discouraged users from using International Mobile Remittances
Keywords: Mobile Money Remittance in East Africa; Technology Acceptance Model; Empirical study; Cronbach alpha